Applications and Sustainability in Groundwater Abstraction in Malaysia (Jurnal Teknologi (Sciences & Engineering), 2015)
Most major cities in Malaysia face problems of clean and safe water supply. The blame is on the population boom, industrialisation, pollution plus climate change. It becomes more complicated with uncontrolled usage, public’s ignorance and ineffective water management. These problems have led to higher dependencies towards alternative usage of groundwater to serve the needs of public, agricultural sector and the industries. Groundwater usage must be abstracted sustainably to avoid short and long term effects. This exploratory qualitative study analyses several aspects: (a) existing documents on Malaysian water management (b) documents on Malaysian groundwater governance; (c) applications and enforcements of groundwater governance in states. The analyses are essential in recognising and providing appropriate and effective groundwater governance towards higher consumption in the country especially in industrial sector. Early finding reveals the current groundwater governance lack good management and there are legal vacuums. This paper promotes appropriate groundwater governance and management of policies and strategies at both federal and state level, relevant agencies, stakeholders and local communities in ensuring sustainable groundwater resources usage in Malaysia.